Controlo avançado de sistemas híbridos de armazenamento de energia - Hélder João Loureiro Pereira (2020)
Although electric vehicles are a growing solution and to the pollution resulting from internal combustion vehicles, there are inherent obstacles to these that are preventing their popularity, such as: the decay of the health of the energy storage system resulting from the imbalance between batteries, which results in those with less capacity and worse performance reaching higher temperatures and/or discharging below the limit. They are also affected by peak currents inherent to a typical driving cycle that has moments of acceleration or regenerative braking that put too much strain on the cells. These obstacles provide a short life for the storage system, which is undesirable, since it is an extra cost and a serious source of pollution. It is intended with this dissertation to balance the temperature and SoC and simultaneously minimize the effort generated in the batteries during a normal driving cycle. To this end, we seek to develop an advanced control system for hybrid energy storage systems that combines typical lithium cells with super-capacitors (SC) in order to conciliate their complementary characteristics to increase the life span of the storage system and the driving time. Balancing the transit of power between the battery cells and with the SC in order to minimize the said effort and the divergence of SoC and temperature between the cells. In this dissertation, initially the different types of balancing and hybridization are studied in order to understand their advantages and disadvantages and to allow a detailed understanding of the previously developed system. Then, methods of calculating SoC are sought in order to make it possible to maintain an accurate knowledge of the state of the system. Next, various types of real-time control are considered, from rule-based control to predictive control. And finally, based on what has been studied, a model of the system is developed and a predictive controller is built that aims to minimize losses in the system, variations in temperature and SoC between cells and simultaneously decrease the effort caused in the storage system taking advantage of the hybridization using SC.